Molecular Pathogenesis of Oral Squamous Cell Carcinoma : Implications for Therapy - Choi, S.; Myers, J.N. (Journal of dental research, 2008)
The development of oral squamous cell carcinoma (OSCC) is a multistep process requiring the accumulation of multiple genetic alterations, influenced by a patient’s genetic predisposition as well as by environmental influences, including tobacco, alcohol, chronic inflammation, and viral infection. Tumorigenic genetic alterations consist of two major types: tumor suppressor genes, which promote tumor development when inactivated; and oncogenes, which promote tumor development when activated. Tumor suppressor genes can be inactivated through genetic events such as mutation, loss of heterozygosity, or deletion, or by epigenetic modifications such as DNA methylation or chromatin remodeling. Oncogenes can be activated through overexpression due to gene amplification, increased transcription, or changes in structure due to mutations that lead to increased transforming activity. This review focuses on the molecular mechanisms of oral carcinogenesis and the use of biologic therapy to specifically target molecules altered in OSCC. The rapid progress that has been made in our understanding of the molecular alterations contributing to the development of OSCC is leading to improvements in the early diagnosis of tumors and the refinement of biologic treatments individualized to the specific characteristics of a patient’s tumor.